Metabolic and pharmacokinetic studies of scutellarin in rat plasma, urine, and feces - Xing Jian-feng; You Hai-sheng; Dong Ya-lin; Lu Jun; Chen Si-ying; Zhu Hui-fang; Dong Qian; Wang Mao-yi; Dong Wei-hua (Acta Pharmacologica Sinica, 2016)
Aim: To study the metabolic and pharmacokinetic profile of scutellarin, an active component from the medical plant Erigeron breviscapus (Vant) Hand-Mazz, and to investigate the mechanisms underlying the low bioavailability of scutellarin though oral or intravenous administration in rats. Methods: HPLC method was developed for simultaneous detection of scutellarin and scutellarein (the aglycone of scutellarin) in rat plasma, urine and feces. The in vitro metabolic stability study was carried out in rat liver microsomes from different genders. Results: After a single oral dose of scutellarin (400 mg/kg), the plasma concentrations of scutellarin and scutellarein in female rats were significantly higher than in male ones. Between the female and male rats, significant differences in AUC, tmax2 and Cmax2 for scutellarin were found. The pharmacokinetic parameters of scutellarin in the urine also showed significant gender differences. After a single oral dose of scutellarin (400 mg/kg), the total percentage excretion of scutellarein in male and female rats was 16.5% and 8.61%, respectively. The total percentage excretion of scutellarin and scutellarein in the feces was higher with oral administration than with intravenous administration. The in vitro t1/2 and CLint value for scutellarin in male rats was significantly higher than that in female rats. Conclusion: The results suggest that a large amount of ingested scutellarin was metabolized into scutellarein in the gastrointestinal tract and then excreted with the feces, leading to the extremely low oral bioavailability of scutellarin. The gender differences of pharmacokinetic parameters of scutellarin and scutellarein are due to the higher CLint and lower absorption in male rats.